I can see what you are doing: Action familiarity and affordance promote recovery from extinction. - Riddoch, M; Humphreys, G; Hickman, M; Clift, J; Daly, A; Colin, J (2006)
We assessed the effects of three factors on recovery from extinction in patients with lesions including the posterior parietal lobe: (a) whether objects were frequently used together in action versus whether they could be used in action together; (b) whether there was an effect of positioning objects for action; and (c) whether the surface properties of objects mediated performance. There was greater recovery from extinction for objects used frequently together, along with effects produced by objects that could be used together. There were also positive effects of correctly positioning objects for action. There were no effects of surface information on the benefit of reporting both members of a pair, though there were some effects on error trials. The results provide positive evidence for an effect on attention of affordances based on objects falling in plausible co-locations for action. Such affordances may also be influenced by the frequency with which objects are used together and can be generated from edge-based representations of objects (surface colour and depth are not necessary). However, surface-based representations may influence the speed with which action-related properties of objects engage attention.